(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2014)
The Malay manuscripts on firearms are fundamental sources of indigenous knowledge with regard to the firearms technological know-how of the Malays in the past. Although much research has been done on Malay firearms technology, Malay manuscripts are rarely referred to despite being authoritative and pertinent sources of reference. Its very existence is little known to the masses; and this is most probably the one single cause that impeded researchers from exploring the extensive data in the manuscripts. This article aims to disclose the contents of the manuscripts through the description of the important details they hold. This was done by means of amassing the manuscripts on firearms from several archives throughout Malaysia, followed by a critical analysis of the texts. The findings obtained were then classified into relevant topics and subject matter. Finally, it was found that the content in firearms manuscripts forms a primary ethnohistorical source that is vital to the study of technology in the context of the Malay traditional epistemology. Through the study of its discourse, data can be harnessed to help understand the capabilities and intellectual capacity of the Malays in the handling of firearms technology according to their spatio-temporal sphere, based on the cultural meanings which spring from their belief system and world view, set in their cultural setting. Manuskrip ilmu bedil merupakan sumber maklumat peribumi yang penting untuk mengungkapkan tentang teknologi senjata api yang pernah dipraktikkan oleh orang Melayu suatu ketika dahulu. Dalam sekian banyak kajian yang menyentuh soal teknologi senjata api Melayu, manuskrip ilmu bedil sebagai sumber korpus yang lebih autoritatif sifatnya dalam konteks tersebut jarang sekali dirujuk. Kewujudan manuskrip ilmu bedil masih kurang disedari sehingga menyebabkan data penting yang terkandung di dalamnya tidak dieksplorasi dengan wajar, malah ramai pengkaji mungkin tidak pernah menjangka tentang isi kandungannya. Artikel ini cuba memberikan pendedahan tentang manuskrip tersebut dengan memerihalkan beberapa perincian penting dari segi isi kandungannya. Hal ini dilakukan dengan cara mengumpulkan manuskrip ilmu bedil yang tersimpan di beberapa buah pusat dokumentasi di Malaysia dan kemudian dianalisis isi teksnya sebelum diklasifikasi menurut topik dan subjek tertentu. Akhir sekali, isi teksnya dihubungkan pula dengan persoalan etnosejarah teknologi. Dalam kes ini, manuskrip ilmu bedil didapati merupakan sumber etnosejarah yang tidak boleh diabaikan dalam usaha mengkaji teknologi dalam konteks epistemologi tradisional orang Melayu. Menerusi wacananya, manuskrip tersebut secara khusus dapat digunakan untuk memahami keupayaan dan kearifan orang Melayu mengendalikan teknologi senjata api menurut lingkungan spatio-temporal, berdasarkan makna budaya yang ditunjangi oleh sistem kepercayaan dan pandangan dunia dalam latar sejarah kebudayaan mereka.